Quality of life outcomes in pregnancy and postpartum complicated by hypertensive disorders, gestational diabetes, and preterm birth - Mautner, Eva; Greimel, Eva; Trutnovsky, Gerda; Daghofer, Fedor; Egger, Josef W.; Lang, Uwe (Journal of psychosomatic obstetrics and gynaecology, 2009)
Health problems can develop during a pregnancy, turning it into a high risk. The aim of this study was to explore the influence of hypertensive disorders, gestational diabetes, and preterm birth as risk factors for health-related quality of life (HRQL) and depressive symptoms during late pregnancy and postpartum. A prospective, longitudinal study was performed with three assessments. Ninety women were recruited in the study including 29 controls. HRQL was measured using the WHO-QOL-BREF questionnaire. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale (EPDS). Statistical analyses were performed using ANOVA and the chi-square test to explore HRQL and depressive symptoms between three pregnancy risk groups and controls. Women of the preterm group had statistically significant higher depression scores and lower HRQL scores on the physical domain during pregnancy than those without complications. Women with hypertensive disorders showed the second most depressive symptoms. Physical and global HRQL improved and depressive symptoms decreased significantly from late pregnancy and early postpartum period to late postpartum. Pregnant specific health problems, especially the risk for preterm delivery is associated with more depressive symptoms and decreased HRQL in pregnancy. Guidance and communication for these women is important. The counseling should be multi professional to reduce childbirth burdens.